HUBUNGAN ANTARA PROFIL LIPID DAN GANGGUAN MEMORI PADA USIA PARUH BAYA - Fatma Adhayani, Dina Listyaningrum, Hasan Sjahrir (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION THE HIGH LIPID LEVEL HAD BEEN KNOWN TO PLAY A ROLE IN THE DEVELOPMENT OF ALZHEIMER DISEASE AD IN AD MEMORY IMPAIRMENT WAS THE EARLIEST AND THE MOST AFFECTED ASPECT